2018
DOI: 10.1001/jamainternmed.2018.0320
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Breastfeeding for US Physicians Who Are Mothers

Abstract: The benefits of breastfeeding for both women and infants are well established. 1 Despite recommendations from the American Academy of Pediatrics and the World Health Organization, initiating and sustaining lactation remains a challenge for many women. 2 Although 79% of mothers in the United States initiate breastfeeding, only 27% are still breastfeeding at 12 months postpartum. 3 Physicians who are mothers face substantial challenges that may undermine efforts to sustain lactation after they return to work. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 6 publications
4
65
0
1
Order By: Relevance
“…However, in a 2018 JAMA research letter, less than one‐third of physicians report adequacy of breastfeeding according to their personal goal. Physicians experience several common barriers to breastfeeding, including lack of break time, lack of appropriate places to express breast milk, unpredictable clinical schedules, short maternity leaves, and long working hours . Trainees and faculty members have similar barriers, although being a trainee was associated with a larger number of reported barriers .…”
Section: Discussionmentioning
confidence: 99%
“…However, in a 2018 JAMA research letter, less than one‐third of physicians report adequacy of breastfeeding according to their personal goal. Physicians experience several common barriers to breastfeeding, including lack of break time, lack of appropriate places to express breast milk, unpredictable clinical schedules, short maternity leaves, and long working hours . Trainees and faculty members have similar barriers, although being a trainee was associated with a larger number of reported barriers .…”
Section: Discussionmentioning
confidence: 99%
“…There was considerable heterogeneity in the study populations, survey instruments used and outcomes reported. Most studies included only residents (n=22; 43.1%) 18-40 but 10 included a combination of faculty statuses (19.6%) [41][42][43][44][45][46][47][48][49][50][51] (table 2). Most studies combined participants from different practice disciplines (n=28; 54.9%), 20 -22 27 32 35 36 39 41 42 44 45 50 -66 while the remaining studies reported on participants from a single discipline.…”
Section: Characteristics Of Articles Surveys and Interviewsmentioning
confidence: 99%
“…The most frequently cited challenges included inadequate time, schedule inflexibility, and insufficient space. 30 At the point of returning to work, the formerly pregnant surgeon is getting even less sleep than previously, managing the emotions and concerns involved with leaving a new baby at home, and has caloric requirements higher than during pregnancy (500 vs. 300 extra kCal/day). Feeding a newborn generally occurs every 3 hours during the day, and therefore pumping breast milk should occur at roughly the same frequency to avoid diminishing supply.…”
Section: Breastfeedingmentioning
confidence: 99%